Physical Responses of Convective Heavy Rainfall to Future Warming Condition: Case Study of the Hiroshima Event - Hibino, Kenshi; Takayabu, Izuru; Wakazuki, Yasutaka; Ogata, Tomomichi (Frontiers in Earth Science, 2018)
An extreme precipitation event happened at Hiroshima in 2014. Over 200 mm of total rainfall was observed on the night of August 19th, which caused floods and many landslides. The rainfall event was estimated to be a rare event happening once in approximately 30 years. The physical response of this event to the change of the future atmospheric condition, which includes a temperature increase on average and convective stability change, is investigated in the present study using a 27-member ensemble experiment and pseudo global warming downscaling method. The experiment is integrated using the Japan Meteorological Research Institute non-hydrostatic regional climate model. A very high-resolution horizontal grid, 500 m, is used to reproduce dense cumulonimbus cloud formation causing heavy rainfall in the model. The future climate condition determined by a higher greenhouse gas concentration is prescribed to the model, in which the surface air temperature globally averaged is 4 K warmer than that in the preindustrial era. The total amounts of precipitation around the Hiroshima area in the future experiments are closer to or slightly lower than in the current experiments in spite of the increase in water vapor due to theatmospheric warming. The effect of the water vapor increase on extreme precipitation is found to be canceled out by the suppression of convection due to the thermal stability enhancement. The fact that future extreme precipitation like the Hiroshima event is not intensified is in contrast to the well-known result that extreme rainfall tends to be intensified in the future. The results in the present study imply that the response of extreme precipitation to global warming differs for each rainfall phenomenon.